Effects of isometric and dynamic postactivation potentiation protocols on maximal sprint performance - Lim, J. J. H.; Kong, P. W. (The Journal of Strength and Conditioning Research, 2013)
This study examined the effects of 3 types of postactivation potentiation (PAP) protocols (single-joint isometric, multijoint isometric, and multijoint dynamic) on subsequent 10-m, 20-m and 30-m sprint performance in 12 well-trained male track athletes (mean ± SD age = 22.4 ± 3.2 years). The subjects performed 4 protocols in a randomized order on different days as follows: control (4 minutes of passive rest), maximum voluntary isometric knee extension (3 repetitions of 3-second isometric knee extension), maximum voluntary isometric back squat (3 repetitions of 3-second isometric squat), and dynamic back squat (3 repetitions of back squats at 90% 1 repetition maximum). After each protocol, a 4-minute recovery period was incorporated before a 30-m maximal sprint assessment. Maximal sprint times at 10 m, 20 m, and 30 m were measured using timing gates to reflect sprint performance. One-way repeated measures analyses of variance revealed no differences in sprint performance among the 4 protocols at 10-m, 20-m, or 30-m intervals. There were, however, large individual variations in the response to the PAP protocols with some athletes benefiting from the PAP effect and others not. In summary, this study showed no enhancement of short-distance sprint performance after PAP protocols with a 4-minute recovery period, regardless of isometric or dynamics, single-joint or multijoint. Coaches considering the use of PAP protocols to improve sprinting performance of their athletes should exploit the effectiveness of different PAP protocols on an individual basis.